Analisis Pengaruh Return On Assets (ROA), Return On Equity (ROE), Net Profit Margin (NPM), dan Earning Per Share (EPS) Terhadap Harga Saham Perbankan (Studi pada Bank - Manaha, Paulsen William; Herawati, Juni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aimed to determine the effect of financial ratios, represented by ROA, ROE, NPM, and EPS simultaneously or partially, as well as identify and analyze the dominant variables on stock prices private banks listed on the Indonesia Stock Exchange at 2009-2011 period.Â Â This study uses ROA, ROE, NPM, EPS as independent variables and the stock price as the dependent variable. This study is a descriptive study. Descriptive method is a method used to analyze data in ways that describe or depict the data that has been collected as systematically aims to determine the research done and examine the causes certain symptoms. The samples in this study were 19 private banks company of the total population 27 private banks company. The tests in this study are classical assumption comprising, normality test, autocorrelation, heteroscedasticity test and multicollinearity test. In multiple linear regression, testing using the F test is used to indicate whether all the independent variables simultaneously have a significant effect on the dependent variables and t tests were used to see the significance of the effect of independent variables on the dependent variable individually. The results of this study indicate that all the independent variables simultaneously have a significant effect on stock prices. Partial variable ROA, ROE, NPM, and EPS showed a significantÂ effect on stock prices. Dominant variables affecting the stock price is EPS variable. Keywords : Bank, ROA, ROE, NPM, EPS, Share Price